The COVID-19 Athlete Passport: A tool for managing athlete COVID-19 status surrounding the Tokyo 2020 Olympic Games - McLarnon, M.; Heron, N. (The Physician and Sportsmedicine, 2021)
COVID-19 has strongly impacted sporting participation at all levels of competition, with many large-scale events postponed or even cancelled. Mass gatherings at sporting events have also been severely restricted;[1] such gatherings are a known source of infectious disease transmission, with the potential for global spread upon return to home country.[2] Moreover, it has been previously reported from the 2018 Winter Olympics that infectious diseases, in particular respiratory tract infections, may spread readily within the same sporting discipline or team.[2] This presents strong rationale to manage the participating athletes appropriately to prevent further outbreak of COVID-19.